Linear features affect pollination success in experimental plant assemblages - Dongbo Li; Christopher F. Clements; Jane Memmott (Oecologia, 2026)

Multivariate signals of population collapse in a high‐throughput ecological experiment - Francesco Cerini; John Jackson; Duncan O'Brien; Dylan Z. Childs; Christopher F. Clements (Ecology, 2025)
Anticipating population declines is a crucial goal of conservation ecology. Recent conceptual work suggests that populations facing growing stressors should exhibit sequential shifts in behavior, morphology, and abundance before declining to extinction. However, the lack of high‐resolution, multidimensional data has hindered empirical validation of this conceptual work. Using an autonomously monitored, high‐throughput experimental system, we generated individual‐based data on populations of the ciliate Paramecium caudatum forced to collapse due to increasingly stressful conditions. The gradual introduction of a pollutant elicited the predictable sequence of responses—declines in movement speed, followed by declines in body length, emergence of early warning signals of collapse, and finally, abundance declines. Conversely, a press disturbance generated by the introduction of predators did not induce this sequence. The time between the first detectable trait changes and population collapse depended on the statistical approach used, but the sequence remained consistent. Using general additive models, detectable behavioral signals in the polluted populations occurred one generation before abundance‐based early warning signals were detectable, and two generations before abundance decline. We highlight that multivariate monitoring, particularly individual‐based metrics, is crucial for forecasting population declines.

Stability metrics behave predictably across data qualities but are sensitive to community size - Duncan A. O'Brien; Christopher F. Clements (Biological Conservation, 2025)

Novel Regimes of Extreme Climatic Events Trigger Negative Population Rates in a Common Insect - Maria Vives‐Ingla; Pol Capdevila; Christopher F. Clements; Constantí Stefanescu; Jofre Carnicer (Global Change Biology, 2025)
The IPCC predicts that events at the extreme tail of the probability distribution will increase at a higher rate relative to less severe but still abnormal events. Such outlier events are of particular concern due to nonlinear physiological and demographic responses to climatic exposure, meaning that these events are expected to have disproportionate impacts on populations over the next decades (so called low‐likelihood, high‐impact events —LLHI). Because such events are historically rare, forecasting how biodiversity will respond requires mechanistic models that integrate the fundamental processes driving biological responses to our changing climate. Here we built a matrix population model (MPM) from long‐term monitored populations of an insect model species in a Mediterranean area. The model simultaneously integrates the effects of extreme microclimatic heat exposure and drought‐induced host‐plant scarcity on early life stages, a key methodological step forward because these understudied life stages are usually very susceptible to climatic events. This model for the first time allowed us to forecast the demographic impacts that LLHI events will have on a well‐known insect considering their whole life cycle. We found that juveniles were the life stage with the largest relative contribution to population dynamics. In line with field observations, simulated population rates in current climatic regimes were importantly determined by drought impacts, producing a regional mosaic of non‐declining and declining populations. The simulations also indicated that in future, climate scenarios not meeting the Paris Agreement, LLHI heat extremes triggered regionally widespread and severe declines in this currently abundant species. Our results suggest that LLHI events could thus emerge as a critical new —but overlooked— driver of the declines in insect populations, risking the crucial ecosystem functions they perform. We suggest that process‐based and whole‐cycle modelling approaches are a fundamental tool with which to understand the true impacts of climate change.

Restoring spatiotemporal variability to enhance the capacity for dispersal‐limited species to track climate change - Gregory A. Backus; Christopher F. Clements; Marissa L. Baskett (Ecology, 2024)
Climate refugia are areas where species can persist through climate change with little to no movement. Among the factors associated with climate refugia are high spatial heterogeneity, such that there is only a short distance between current and future optimal climates, as well as biotic or abiotic environmental factors that buffer against variability in time. However, these types of climate refugia may be declining due to anthropogenic homogenization of environments and degradation of environmental buffers. To quantify the potential for restoration of refugia‐like environmental conditions to increase population persistence under climate change, we simulated a population's capacity to track their temperature over space and time given different levels of spatial and temporal variability in temperature. To determine how species traits affected the efficacy of restoring heterogeneity, we explored an array of values for species' dispersal ability, thermal tolerance, and fecundity. We found that species were more likely to persist in environments with higher spatial heterogeneity and lower environmental stochasticity. When simulating a management action that increased the spatial heterogeneity of a previously homogenized environment, species were more likely to persist through climate change, and population sizes were generally higher, but there was little effect with mild temperature change. The benefits of heterogeneity restoration were greatest for species with limited dispersal ability. In contrast, species with longer dispersal but lower fecundity were more likely to benefit from a reduction in environmental stochasticity than an increase in spatial heterogeneity. Our results suggest that restoring environments to refugia‐like conditions could promote species' persistence under the influence of climate change in addition to conservation strategies such as assisted migration, corridors, and increased protection.

Planktonic functional diversity changes in synchrony with lake ecosystem state - Duncan A. O'Brien; Gideon Gal; Stephen J. Thackeray; Shin‐ichiro S. Matsuzaki; Christopher F. Clements (Global Change Biology, 2023)
Managing ecosystems to effectively preserve function and services requires reliable tools that can infer changes in the stability and dynamics of a system. Conceptually, functional diversity (FD) appears as a sensitive and viable monitoring metric stemming from suggestions that FD is a universally important measure of biodiversity and has a mechanistic influence on ecological processes. It is however unclear whether changes in FD consistently occur prior to state responses or vice versa, with no current work on the temporal relationship between FD and state to support a transition towards trait‐based indicators. There is consequently a knowledge gap regarding when functioning changes relative to biodiversity change and where FD change falls in that sequence. We therefore examine the lagged relationship between planktonic FD and abundance‐based metrics of system state (e.g. biomass) across five highly monitored lake communities using both correlation and cutting edge non‐linear empirical dynamic modelling approaches. Overall, phytoplankton and zooplankton FD display synchrony with lake state but each lake is idiosyncratic in the strength of relationship. It is therefore unlikely that changes in plankton FD are identifiable before changes in more easily collected abundance metrics. These results highlight the power of empirical dynamic modelling in disentangling time lagged relationships in complex multivariate ecosystems, but suggest that FD cannot be generically viable as an early indicator. Individual lakes therefore require consideration of their specific context and any interpretation of FD across systems requires caution. However, FD still retains value as an alternative state measure or a trait representation of biodiversity when considered at the system level.

Towards the fully automated monitoring of ecological communities - Marc Besson; Jamie Alison; Kim Bjerge; Thomas E. Gorochowski; Toke T. Høye; Tommaso Jucker; Hjalte M. R. Mann; Christopher F. Clements (Ecology Letters, 2022)
High‐resolution monitoring is fundamental to understand ecosystems dynamics in an era of global change and biodiversity declines. While real‐time and automated monitoring of abiotic components has been possible for some time, monitoring biotic components—for example, individual behaviours and traits, and species abundance and distribution—is far more challenging. Recent technological advancements offer potential solutions to achieve this through: (i) increasingly affordable high‐throughput recording hardware, which can collect rich multidimensional data, and (ii) increasingly accessible artificial intelligence approaches, which can extract ecological knowledge from large datasets. However, automating the monitoring of facets of ecological communities via such technologies has primarily been achieved at low spatiotemporal resolutions within limited steps of the monitoring workflow. Here, we review existing technologies for data recording and processing that enable automated monitoring of ecological communities. We then present novel frameworks that combine such technologies, forming fully automated pipelines to detect, track, classify and count multiple species, and record behavioural and morphological traits, at resolutions which have previously been impossible to achieve. Based on these rapidly developing technologies, we illustrate a solution to one of the greatest challenges in ecology: the ability to rapidly generate high‐resolution, multidimensional and standardised data across complex ecologies.

Landscape configuration affects probability of apex predator presence and community structure in experimental metacommunities - Ellie Wolfe; Edd Hammill; Jane Memmott; Christopher F. Clements (Oecologia, 2022)
Biodiversity is declining at an unprecedented rate, highlighting the urgent requirement for well-designed protected areas. Design tactics previously proposed to promote biodiversity include enhancing the number, connectivity, and heterogeneity of reserve patches. However, how the importance of these features changes depending on what the conservation objective is remains poorly understood. Here we use experimental landscapes containing ciliate protozoa to investigate how the number and heterogeneity in size of habitat patches, rates of dispersal between neighbouring patches, and mortality risk of dispersal across the non-habitat ‘matrix’ interact to affect a number of diversity measures. We show that increasing the number of patches significantly increases γ diversity and reduces the overall number of extinctions, whilst landscapes with heterogeneous patch sizes have significantly higher γ diversity than those with homogeneous patch sizes. Furthermore, the responses of predators depended on their feeding specialism, with generalist predator presence being highest in a single large patch, whilst specialist predator presence was highest in several-small patches with matrix dispersal. Our evidence emphasises the importance of considering multiple diversity measures to disentangle community responses to patch configuration.

Global patterns of resilience decline in vertebrate populations - Pol Capdevila; Nicola Noviello; Louise McRae; Robin Freeman; Christopher F. Clements (Ecology Letters, 2022)
Maintaining the resilience of natural populations, their ability to resist and recover from disturbance, is crucial to prevent biodiversity loss. However, the lack of appropriate data and quantitative tools has hampered our understanding of the factors determining resilience on a global scale. Here, we quantified the temporal trends of two key components of resilience—resistance and recovery—in >2000 population time‐series of >1000 vertebrate species globally. We show that the number of threats to which a population is exposed is the main driver of resilience decline in vertebrate populations. Such declines are driven by a non‐uniform loss of different components of resilience (i.e. resistance and recovery). Increased anthropogenic threats accelerating resilience loss through a decline in the recovery ability—but not resistance—of vertebrate populations. These findings suggest we may be underestimating the impacts of global change, highlighting the need to account for the multiple components of resilience in global biodiversity assessments.

Corridor quality affects net movement, size of dispersers, and population growth in experimental microcosms - Dongbo Li; Christopher F. Clements; Isobel L. G. Shan; Jane Memmott (Oecologia, 2021)
Corridors are expected to increase species dispersal in fragmented habitats. However, it remains unclear how the quality of corridors influences the dispersal process, and how it interacts with corridor length and width. Here we investigate these factors using a small-scale laboratory system where we track the dispersal of the model organism Collembola Folsomia candida . Using this system, we study the effects of corridor length, width, and quality on the probability of dispersal, net movement, body size of dispersers, and the rate of change in population size after colonization. We show that corridor quality positively affected dispersal probability, net movement, and the rate of change in population size in colonised patches. Moreover, corridor quality significantly affected the size of dispersers, with only larger individuals dispersing through poor quality corridors. The length and width of corridors affected both the rate at which populations increased in colonised patches and the net number of individuals which dispersed, suggesting that these physical properties may be important in maintaining the flow of individuals in space. Our results thus suggest that corridor quality can have an important role in determining not only the probability of dispersal occurs but also the phenotypes of the individuals which disperse, with concomitant effects on the net movement of individuals and the rate of change in population size in the colonised patches.

Imperfect detection alters the outcome of management strategies for protected areas - Edd Hammill; Christopher F. Clements (Ecology Letters, 2020)
Designing protected area configurations to maximise biodiversity is a critical conservation goal. The configuration of protected areas can significantly impact the richness and identity of the species found there; one large patch supports larger populations but can facilitate competitive exclusion. Conversely, many small habitats spreads risk but may exclude predators that typically require large home ranges. Identifying how best to design protected areas is further complicated by monitoring programs failing to detect species. Here we test the consequences of different protected area configurations using multi‐trophic level experimental microcosms. We demonstrate that for a given total size, many small patches generate higher species richness, are more likely to contain predators, and have fewer extinctions compared to single large patches. However, the relationship between the size, number of patches, and species richness was greatly affected by insufficient monitoring, and could lead to incorrect conservation decisions, especially for higher trophic levels.

Indicators of transitions in biological systems - Christopher F. Clements; Arpat Ozgul (Ecology Letters, 2018)
In the face of global biodiversity declines, predicting the fate of biological systems is a key goal in ecology. One popular approach is the search for early warning signals ( EWS s) based on alternative stable states theory. In this review, we cover the theory behind nonlinearity in dynamic systems and techniques to detect the loss of resilience that can indicate state transitions. We describe the research done on generic abundance‐based signals of instability that are derived from the phenomenon of critical slowing down, which represent the genesis of EWS s research. We highlight some of the issues facing the detection of such signals in biological systems – which are inherently complex and show low signal‐to‐noise ratios. We then document research on alternative signals of instability, including measuring shifts in spatial autocorrelation and trait dynamics, and discuss potential future directions for EWS s research based on detailed demographic and phenotypic data. We set EWS s research in the greater field of predictive ecology and weigh up the costs and benefits of simplicity vs. complexity in predictive models, and how the available data should steer the development of future methods. Finally, we identify some key unanswered questions that, if solved, could improve the applicability of these methods.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Geographical distribution patterns of Carcharocles megalodon over time reveal clues about extinction mechanisms - Catalina Pimiento; Bruce J. MacFadden; Christopher F. Clements; Sara Varela; Carlos Jaramillo; Jorge Velez‐Juarbe; Brian R. Silliman (Journal of Biogeography, 2016)
Aim Given its catastrophic consequences, the extinction of apex predators has long been of interest to modern ecology. Despite major declines, no present‐day species of marine apex predator has yet become extinct. Because of their vulnerability, understanding the mechanisms leading to their extinction in the past could provide insight into the natural factors that interact with human threats to drive their loss. We studied the geographical distribution patterns of the extinct macro‐predatory shark Carcharocles megalodon in order to elucidate its pathway to extinction. Location World‐wide from the Miocene to the Pliocene ( c. 23–2.6 Ma). Methods A meta‐analysis of C. megalodon occurrence records was performed using the Paleobiology Database as a platform. The data were binned into geological time slices, and the circular home range around each data point was mapped in reconstructions made in GP lates. We then quantitatively assessed the species' geographical range and global abundance over time, and the relationship between distribution and climate. Results The pathway to extinction of C. megalodon probably started in the late Miocene with a decrease in its global abundance. This decrease was then followed by a decline in its geographical range during the Pliocene. Although the extinction of C. megalodon has been attributed to climate change, we found no evidence of direct effects of global temperature. Instead, we found that the collapse in geographical distribution coincided mainly with a drop in the diversity of filter‐feeding whales and the appearance of new competitors (large predatory whales and the great white shark). Main conclusions This research represents the first study of the distributional trends of an extinct, cosmopolitan apex predator in deep‐time. Our results suggest that biotic factors, and not direct temperature limitations, were probably the primary drivers of the extinction of the largest marine apex predators that ever lived.

Paradigms for parasite conservation - Eric R. Dougherty; Colin J. Carlson; Veronica M. Bueno; Kevin R. Burgio; Carrie A. Cizauskas; Christopher F. Clements; Dana P. Seidel; Nyeema C. Harris (Conservation Biology, 2016)
Parasitic species, which depend directly on host species for their survival, represent a major regulatory force in ecosystems and a significant component of Earth's biodiversity. Yet the negative impacts of parasites observed at the host level have motivated a conservation paradigm of eradication, moving us farther from attainment of taxonomically unbiased conservation goals. Despite a growing body of literature highlighting the importance of parasite‐inclusive conservation, most parasite species remain understudied, underfunded, and underappreciated. We argue the protection of parasitic biodiversity requires a paradigm shift in the perception and valuation of their role as consumer species, similar to that of apex predators in the mid‐20th century. Beyond recognizing parasites as vital trophic regulators, existing tools available to conservation practitioners should explicitly account for the unique threats facing dependent species. We built upon concepts from epidemiology and economics (e.g., host‐density threshold and cost‐benefit analysis) to devise novel metrics of margin of error and minimum investment for parasite conservation. We define margin of error as the risk of accidental host extinction from misestimating equilibrium population sizes and predicted oscillations, while minimum investment represents the cost associated with conserving the additional hosts required to maintain viable parasite populations. This framework will aid in the identification of readily conserved parasites that present minimal health risks. To establish parasite conservation, we propose an extension of population viability analysis for host–parasite assemblages to assess extinction risk. In the direst cases, ex situ breeding programs for parasites should be evaluated to maximize success without undermining host protection. Though parasitic species pose a considerable conservation challenge, adaptations to conservation tools will help protect parasite biodiversity in the face of an uncertain environmental future.

Linking Indices for Biodiversity Monitoring to Extinction Risk Theory - MICHAEL A. MCCARTHY; ALANA L. MOORE; JOCHEN KRAUSS; JOHN W. MORGAN; CHRISTOPHER F. CLEMENTS (Conservation Biology, 2014)
Biodiversity indices often combine data from different species when used in monitoring programs. Heuristic properties can suggest preferred indices, but we lack objective ways to discriminate between indices with similar heuristics. Biodiversity indices can be evaluated by determining how well they reflect management objectives that a monitoring program aims to support. For example, the Convention on Biological Diversity requires reporting about extinction rates, so simple indices that reflect extinction risk would be valuable. We developed 3 biodiversity indices that are based on simple models of population viability that relate extinction risk to abundance. We based the first index on the geometric mean abundance of species and the second on a more general power mean. In a third index, we integrated the geometric mean abundance and trend. These indices require the same data as previous indices, but they also relate directly to extinction risk. Field data for butterflies and woodland plants and experimental studies of protozoan communities show that the indices correlate with local extinction rates. Applying the index based on the geometric mean to global data on changes in avian abundance suggested that the average extinction probability of birds has increased approximately 1% from 1970 to 2009. Conectando Índices para el Monitoreo de la Biodiversidad con la Teoría de Riesgo de Extinción

Effects of Recent Environmental Change on Accuracy of Inferences of Extinction Status - CHRISTOPHER F. CLEMENTS; BEN COLLEN; TIM M. BLACKBURN; OWEN L. PETCHEY (Conservation Biology, 2014)
Correctly classifying a species as extinct or extant is of critical importance if current rates of biodiversity loss are to be accurately quantified. Observing an extinction event is rare, so in many cases extinction status is inferred using methods based on the analysis of records of historic sighting events. The accuracy of such methods is difficult to test. However, results of recent experiments with microcosm communities suggest that the rate at which a population declines to extinction, potentially driven by varying environmental conditions, may alter one's ability accurately to infer extinction status. We tested how the rate of population decline, driven by historic environmental change, alters the accuracy of 6 commonly applied sighting‐based methods used to infer extinction. We used data from small‐scale experimental communities and recorded wild population extirpations. We assessed how accuracy of the different methods was affected by rate of population decline, search effort, and number of sighting events recorded. Rate of population decline and historic population size of the species affected the accuracy of inferred extinction dates; however, faster declines produced more accurate inferred dates of extinction, but only when population sizes were higher. Optimal linear estimation (OLE) offered the most reliable and robust estimates, though no single method performed best in all situations, and it may be appropriate to use a different method if information regarding historic search efforts is available. OLE provided the most accurate estimates of extinction when the number of sighting events used was >10, and future use of this method should take this into account. Data from experimental populations provide added insight into testing techniques to discern wild extirpation events. Care should be taken designing such experiments so that they mirror closely the abundance dynamics of populations affected by real‐world extirpation events. Efectos del Cambio Ambiental Reciente sobre la Precisión de las Inferencias sobre el Estado de Extinción

Public interest in the extinction of a species may lead to an increase in donations to a large conservation charity - Christopher F. Clements (Biodiversity and Conservation, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)